The effect of sulbutiamine on postoperative recovery and cognitive functions in geriatric patients [Sulbutiyaminin Yaşli Hastalarda Postoperatif Derlenme Dönemi ve Kognitif Fonksiyonlara Etkisi] - (:unkn) unknown (Anestezi Dergisi, 2006)
Objective: To investigate the effects of preoperative sulbutiamine administration on recovery time, sleep-conciousness cycle, and cognitive functions in geriatric patients. Method: Forty patients, ASA group I-II , above 60 years of age and scheduled for elective peripheral surgery were enrolled in this study. Patients were randomly assigned to control (n=20) and sulbutiamine (n=20) groups. 200 mg of sulbutiamine was administred peroral twice a day for 14 days prior to surgery. Recovery time, Aldrete scores, postoperative cognitive functions (standard mini mental test scores) and sleep-consciousness cycle abnormalities were recorded and compared statistically using Student's t-test, ki-square and Mann-Whitney U tests. Results: Recovery time was significantly shorter in the sulbutia mine group compared to the control group (p<0.01). The incidence of sleep-conciousness cycle abnormalities during postoperative days 1 and 2 was higher in the control group than in the sulbutiamine group (p<0.05). While mini mental test scores were similar in the preoperative period, they were significantly higher in the drug group at 1, 2 and 4. hours after the operation and at the postoperative day 1 (p<0.01). Aldrete scores in the sulbutiamine treated group were significantly higher at 5, 10 and 15 minutes postoperative (p<0.01). Conclusion: Preoperative admi nistration of sulbutiamine in geriatric patients shortened time to regain consciousness and improved postoperative cognitive functions.
Keywords: Cognitive functions; Mini mental test; Sulbutiamine